Documenting a Province : the Archives of Ontario at 100/le centenaire des Archives publiques d'Ontario - Ontario, Archivist of (University of Toronto Press, 2014)
Showcasing a broad cross-section of items, Documenting a Province: The Archives of Ontario at 100, commemorates Ontario's heritage through promotion and explanation of the Archives' collections.